1997
DOI: 10.1006/jmsc.1996.0203
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ivermectin, used to control sea lice on caged farmed salmonids, on infaunal polychaetes

Abstract: . 1997. The effects of ivermectin, used to control sea lice on caged farmed salmonids, on infaunal polychaetes. -ICES Journal of Marine Science, 54: 276-279.The mortality of benthic polychaetes was examined after treatment with ivermectin, an agent to control sea lice on caged salmonids. Ivermectin had a significant effect on polychaete mortality at applications of 81 and 810 g m 2 . The potential exists for toxic levels of ivermectin to accumulate in sediments at fish farm sites if this product is used freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…comparing mussel-farm edge and 25 m fish-farm distance). The differences in biodiversity impacts may be as a consequence of differing aquaculture practices, for example the use of chemotheraputants and/or agents to control net-fouling on Scottish fish-farms [55].…”
Section: Discussionmentioning
confidence: 99%
“…comparing mussel-farm edge and 25 m fish-farm distance). The differences in biodiversity impacts may be as a consequence of differing aquaculture practices, for example the use of chemotheraputants and/or agents to control net-fouling on Scottish fish-farms [55].…”
Section: Discussionmentioning
confidence: 99%
“…commun. ) and experimental laboratory studies (Black et al 1997;Collier & Pinn 1998), suggested that ivermectin was less toxic to multispecies benthic communities than had been inferred from single species acute tests. Grant & Briggs (1998a,b) reported additional toxicity data, and concluded that further information about the persistence, bioavailability and toxicity of ivermectin under ®eld conditions was required to be able to justify the continued use of ivermectin.…”
Section: Environmental Riskmentioning
confidence: 97%
“…Mortalities of the polychaete, Capitella capitata have been observed in cores dosed experimentally with ivermectin (78–780 mg m −2 ) over a 3‐week period (Black, Fleming, Nickell & Oereira 1997). Another experimental study exposed intertidal communities (unaffected by fish farming) to ivermectin (8–80 mg m −2 ) and reported significant effects on numbers and biomass of members of the benthic community (Collier & Pinn 1998).…”
Section: Ivermectinmentioning
confidence: 99%
See 2 more Smart Citations